Exemplary Canadians? How Two Canadian Women Remember Their Roles in a Cold War Military Family - Campbell, Isabel (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2016)
This piece examines the constructed memories of the wife and a daughter of an air force subaltern, using oral history interviews to highlight their unique voices and explore their lived realities. Whole life history methodology reveals complexities and contradictions with regard to idealized families, generational differences, and polarized gender roles that might remain otherwise hidden when relying primarily on archival sources. This process peels back the idealized middle-class family of post-war elite proponents and it exposes points of intersection and difference with the historiography of Canadian Cold War families in general, and military families in particular. Their contrasting stories are not intended to represent the thousands of individual military family lives; rather, the reiteration of these oral histories highlights the unique McMillan family stories and reveals how military service, personnel policies, gender, age, class, education, culture, geographic location, place in the family, and individual personality and capabilities played out in their particular lives.